Growth-regulating factor 15 is required for leaf size control in Populus. (11th October 2018) - Zhou, Houjun; Song, Xueqin; Wei, Kaili; Zhao, Yanqiu; Jiang, Cheng; Wang, Jinnan; Tang, Fang; Lu, Mengzhu
Abstract: Growth-regulating factors (GRFs) are involved in various developmental events, particularly leaf development. However, the functions of GRFs in woody plants remain elusive. In this study, functional characterization of GRF15 in Populus was performed. Most GRFs are preferentially expressed in young leaves. As GRF15 was expressed at the highest level and with highest ratio in Populus species with large leaves, this gene was investigated through transgenic analyses. Promotor-β-glucuronidase analysis revealed expression of GRF15 at the leaf expansion zone. Additionally, GRF15 was found to be localized in the nucleus and regulated by miR396. Leaf size and palisade cell size were significantly increased and decreased in GRF15 -overexpressing and dominant repression lines, respectively. Consistently, expression of EXPA11a, a homolog of cell-expansion marker EXPA11 in Arabidopsis, was strongly upregulated and downregulated in the GRF15- overexpressing and dominant repression lines, respectively, which was further manifested by activation of EXPA11a by GRF15 in transactivation assays. Therefore, GRF15 is required for leaf size control and primarily modulates cell expansion during leaf development in Populus .